2002
DOI: 10.1093/ps/81.10.1598
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electrolyzed oxidizing water with various antimicrobial interventions to reduce Salmonella species on poultry

Abstract: Foodborne pathogens in cell suspensions or attached to surfaces can be reduced by electrolyzed oxidizing (EO) water; however, the use of EO water against pathogens associated with poultry has not been explored. In this study, acidic EO water [EO-A; pH 2.6, chlorine (CL) 20 to 50 ppm, and oxidation-reduction potential (ORP) of 1,150 mV], basic EO water (EO-B; pH 11.6, ORP of -795 mV), CL, ozonated water (OZ), acetic acid (AA), or trisodium phosphate (TSP) was applied to broiler carcasses inoculated with Salmone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(118 citation statements)
references
References 32 publications
5
107
1
5
Order By: Relevance
“…Organic acids spray such as lactic acid and acetic acid at 1-2 % are also effective in reducing bacterial load in poultry but higher concentration of these acids tends to bleach the carcasses. Spraying or adding in chill water containing chemicals such as trisodium phosphate at 8-12 % (Capita et al 2002), cetylpyridinium chloride at 0.5 %, ozonated water @ 0.03 ppm for chill water (Fabrizio et al 2002), hydrogen peroxide (5 % for spray and 0.5-1.5 % for chill water), bacteriocins and activated lactoferrin are also permitted for decontamination of poultry carcass (Loretz et al 2010). Reducing carcass temperature to <4°C in chill water quickly after slaughter is the primary means of preventing proliferation of pathogens in poultry (Table 2).…”
Section: Postharvest Intervention Technologiesmentioning
confidence: 99%
“…Organic acids spray such as lactic acid and acetic acid at 1-2 % are also effective in reducing bacterial load in poultry but higher concentration of these acids tends to bleach the carcasses. Spraying or adding in chill water containing chemicals such as trisodium phosphate at 8-12 % (Capita et al 2002), cetylpyridinium chloride at 0.5 %, ozonated water @ 0.03 ppm for chill water (Fabrizio et al 2002), hydrogen peroxide (5 % for spray and 0.5-1.5 % for chill water), bacteriocins and activated lactoferrin are also permitted for decontamination of poultry carcass (Loretz et al 2010). Reducing carcass temperature to <4°C in chill water quickly after slaughter is the primary means of preventing proliferation of pathogens in poultry (Table 2).…”
Section: Postharvest Intervention Technologiesmentioning
confidence: 99%
“…The alkaline EO water so collected has a pH of approximately 11.4 and ORP of 795 mV, while acidic EO water has a pH of approximately 2.6, ORP of 1150 mV and a chlorine concentration 40 and 90 ppm. EO water has been utilized to disinfect kitchen cutting boards, and other surfaces, fresh cut vegetables, alfalfa seeds and sprouts, broccoli, strawberry, lettuce, tomatoes, apple and poultry [6,7]. Electrolyzed oxidizing water (EOW) has been reported to have strong bactericidal effects on many pathogenic bacteria, such as Escherichia coli O157:H7 [8], Listeria monocytogenes [9], Bacillus cereus [10], and Salmonella sp.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to the effect of alkaline electrolysis water [107], the author suggested that using amended salt solutions would improve the biocidal effect of electrolyzing. Further studies have suggested the higher biocide effect of acidic water and also suggested alkaline water to be used in cleaning and degreasing before application of acidic electrolyzed water [108][109][110][111][112].…”
Section: Anions Of CLmentioning
confidence: 99%